2011
DOI: 10.4236/ce.2011.23026
|View full text |Cite
|
Sign up to set email alerts
|

Creating Student Engagement? HMM: Teaching and Learning with Humor, Music, and Movement

Abstract: With growing concerns about student engagement, the theme of creative teaching and learning provides an excellent catalyst to consider methods that enhance students' classroom experiences. Good teaching is akin to weaving a fabric of connectedness between student, teacher, and subject (Palmer, 2007). Teacher-student connection and student engagement are the two most important ingredients in teaching (Lowman, 1995). This paper explores three effective methods of weaving the fabric and engaging students in highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
(15 reference statements)
1
15
0
4
Order By: Relevance
“…MITA has a strong student focus and it was noted that the participants engaged enthusiastically with all the activities during the clinical skills sessions. Having activities that are fun have been found to help increase student learning and this result is similar to other studies (Baid & Lambert 2010;Strean 2011). Baid and Lambert (2010) conducted a critical evaluation of the literature to explore the use of humour and 'fun' teaching strategies within nursing education.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…MITA has a strong student focus and it was noted that the participants engaged enthusiastically with all the activities during the clinical skills sessions. Having activities that are fun have been found to help increase student learning and this result is similar to other studies (Baid & Lambert 2010;Strean 2011). Baid and Lambert (2010) conducted a critical evaluation of the literature to explore the use of humour and 'fun' teaching strategies within nursing education.…”
supporting
confidence: 55%
“…Strean (2011) found that music enhanced student engagement, humour reduced anxiety and promoted a relaxed environment and movement increased energy levels and this is strongly supported in MITA and brain based learning.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…O humor é uma boa forma de desviar a atenção desses problemas", ou seja, embora a educação seja um negócio sério isso não quer dizer que as atividades educacionais não possam ser divertidas (Strean, 2011).…”
Section: Mauro: Vocês Poderiam Me Falar Um Pouco Mais Disso E Porque unclassified